Die Erinnerung an die Sächsische Schweiz in den Reisetagebüchern der Schwester Florentyna und Symforoza Krzyżanowska - Katarzyna Król (Góry, Literatura, Kultura)
In the first half of the 19th century, one of the corners of Europe most eagerly visited by Poles was Saxon Switzerland, as its natural and landscape values aroused not only admiration but also amazement among Polish tourists. This is evidenced, for instance, by various travel accounts, among which it is worth mentioning the travel diaries of two young girls—sisters Florentyna and Symforoza Krzyżanowska, which remain in manuscripts to this day. These notes contain fragments devoted to their trip to Saxon Switzerland in September 1829, which provided them with many unforgettable experiences. This expedition lasted two days, during which the young travelers visited, among others, Pillnitz, Bastei, Kuhstall, Schandau, Lichtenhain and Pirna. They explored the land surrounding them from three different perspectives: from the heights of the mountain hills, lowland areas and from the riverbed. They followed a marked and popular trail, and covered individual stages of the journey by carriage, on foot or by barge. On the pages of their diaries, they recorded sightseeing information, comments on the peculiarities of nature, observations on amenities for tourists, and details regarding the methods, conditions and time of the expedition. The descriptions left by Florentyna and Symforoza Krzyżanowska are not only a noteworthy source for studies on the issue of the presence of Poles in Saxon Switzerland, but also an interesting testimony to the fascination with the mountain landscape in the first half of the 19th century. They should also be considered an interesting example of girls’ diary writing, the true value of which can only be revealed by further research.